2004
DOI: 10.1289/ehp.7287
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal DDT Exposure in Relation to Anthropometric and Pubertal Measures in Adolescent Males

Abstract: DDT (dichlorodiphenyltrichloroethane), a pesticide once used widely in agriculture and now limited to public health use, remains a controversial chemical because of a combination of benefits and risks. DDT or its breakdown products are ubiquitous in the environment and in humans. Compounds in the DDT family have endocrine actions and have been associated with reproductive toxicity. A previous study reported associations between prenatal exposure to p,p′-DDE [1,1-dichloro-2,2-bis(p-chlorophenyl)-ethylene] and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 53 publications
(58 reference statements)
6
65
2
1
Order By: Relevance
“…Reproductive effects in humans affecting birth weight, fertility, and duration of lactation, have not been consistently demonstrated (Beard, 2006;Gladen and Rogan, 1995;Jusko et al, 2006), although the risk for preterm delivery may be related to maternal DDE levels (Longnecker et al, 2001). Epidemiologic studies of children with environmental exposure to DDT and DDE have not demonstrated neurologic or developmental abnormalities (Gladen et al, 2004;Jusko et al, 2006;Longnecker et al, 2002;Mariussen and Fonnum, 2006). Several reviews of cancer epidemiologic studies have concluded that a link between DDT and breast cancer is inconclusive (Beard, 2006;Calle et al, 2002;Snedeker, 2001).…”
Section: Selected Percentilesmentioning
confidence: 99%
“…Reproductive effects in humans affecting birth weight, fertility, and duration of lactation, have not been consistently demonstrated (Beard, 2006;Gladen and Rogan, 1995;Jusko et al, 2006), although the risk for preterm delivery may be related to maternal DDE levels (Longnecker et al, 2001). Epidemiologic studies of children with environmental exposure to DDT and DDE have not demonstrated neurologic or developmental abnormalities (Gladen et al, 2004;Jusko et al, 2006;Longnecker et al, 2002;Mariussen and Fonnum, 2006). Several reviews of cancer epidemiologic studies have concluded that a link between DDT and breast cancer is inconclusive (Beard, 2006;Calle et al, 2002;Snedeker, 2001).…”
Section: Selected Percentilesmentioning
confidence: 99%
“…[2] No studies investigating the effect of currently registered agricultural pesticides on pubertal growth were found in the literature, but there is laboratory and epidemiological evidence of reduced height measurements among DDT-exposed boys, although results are contradictory, as discussed earlier. [6][7][8][9][10] …”
Section: Discussionmentioning
confidence: 99%
“…However, when the study was repeated 4 years later on boys born during the period when DDT was used, no associations were found between p,p'-DDE and anthropometric measurements. [7] On the other hand, a prospective study conducted in Germany [8] showed no effect on the height of boys, although reduced height among girls was associated with exposure to higher postnatal childhood p,p'-DDE concentrations. Also, a prospective cohort study done in the USA revealed significantly reduced height among boys between ages 4 and 7 years in the high-exposure group.…”
mentioning
confidence: 97%
“…In a subsequent analysis, using follow-up data from 304 males, enrolled at birth between 1960 − 1965, who had been followed to adolescence in the US Perinatal Collaborative Project, Gladen (Gladen et al, 2004) did not see any effect of prenatal DDT exposure on growth at puberty, and so the large effect seen in North Carolina remains unconfirmed.…”
Section: Adolescent Growth and Sexual Maturationmentioning
confidence: 95%